Water risk hotspots for agriculture. (OECD studies on water., 2017)
Agriculture is expected to face increasing water risks that will impact production, markets, trade and food security - risks that can be mitigated with targeted policy actions on water hotspots. This report develops the hotspot approach, provides an application at the global scale, and presents a mitigation policy action plan. The People's Republic of China, India and the United States are identified as countries facing the greatest water risks for agriculture production globally. A global simulation shows that, in the absence of action, water risks in Northeast China, Northwest India and the Southwest United States in particular could have significant production, price and trade consequences. Agriculture water risks could also result in broader socio-economic and food security concerns. Farmers, agro food companies, and governments can all play a role in responding to water risks at hotspot locations. A three-tier policy action plan is proposed to confront water risk hotspots, encompassing targeted responses, adapted national policies, strengthened market integration and international collaboration.